The relationship between interpersonal conflict causal factors and job performance / Hazwaniqaisara Adenan - Adenan, Hazwaniqaisara (Faculty of Business and Management, 2018)
Harmonious workplace and good relationship among member of the organization is a dream for every employee. However, it is difficult to maintain the harmonious of the workplace because every people have their own personality, opinion and idea. The aim of this study is to identify the most significant interpersonal conflict causal factors with job performance in School of Graduates Studies, Universiti Tekonologi Malaysia, Johor Bahru. In this study, researcher used 3 causal factors which are job stress, communication and workplace incivility. Questionnaire was used in collecting the data from the respondents. The population of the respondents for this study are 49 staffs who are working in School of Graduates Studies, Universiti Teknologi Malaysia, Johor Bahru. 44 questionnaires were successfully distributed and 40 returned questionnaire were used in analysing the data. Descriptive, Normality, Reliability, Regression analysis were used to analyse the data findings. The result from this study shows that communication is the most significant factors that could influence job performance. There is negative relationship between job stress and job performance. Workplace incivility has negative relationship with the job performance. In addition, an efficient communicative practice in the workplace and professionalism training are recommended to resolve the problem.